Pengembangan SDM Berkualitas : Kunci Sukses Institusi Pendidikan - Ardevi Artamevia; Dwi Surya; Tasya Kamila Fiti; Hesti Kusumaningrum (Lembaga Pengembangan Kinerja Dosen, 2025)
This article addresses the importance of developing high-quality human resources (HR) in educational institutions and how this is key to success. The main issue discussed is the challenges in enhancing HR quality amidst the rapidly changing educational landscape. The objective of this article is to explore effective strategies for HR development and identify its impact on institutional performance. The methods used include literature review and case analysis from various educational institutions. The findings reveal that competency-based approaches and continuous training significantly improve teaching and managerial quality. The conclusion emphasizes that educational institutions that succeed in HR development will have a competitive advantage and achieve better educational outcomes.